Penerapan Model Pendidikan Karakter Pengajaran Vokasi (Modikar Pekasi) Kelompok Mata Kuliah Teori Kejuruan di FT UNY - Rosanti Kusuma; Amat Jaedun (Universitas Negeri Yogyakarta, 2022)
ABSTRACTThe purpose of this study was to determine: (1) the understanding of FT UNY lecturers on MODIKAR PEKASI; (2) practical application of MODIKAR PEKASI in teaching vocational theory courses at FT UNY; and (3) the effectiveness of the theoretical application of MODIKAR PEKASI in integrating character values in group teaching of vocational theory courses at the FT UNY. The data were collected using descriptive quantitative methods with the type of survey research through questionnaire, with a lecturer who teaches vocational theory courses at the FT UNY as respondents. Quantitative data analysis used descriptive statistics, while qualitative data used thematic analysis. The results showed: (1) the lecturers' understanding of MODIKAR PEKASI was in the